Assessing progress made toward shared agricultural transformation objectives in Mozambique - Benson, Todd; Mogues, Tewodaj; Woldeyohannes, Sileshi (International Food Policy Research Institute, 2014)
What has been the recent performance of the agricultural sector in Mozambique and the progress made thus far toward achieving the objectives established under the Comprehensive Africa Agriculture Development Programme (CAADP) initiative for Mozambique that began in late-2011?